(3fTCJgG hGJLGgGJgG heLGdGJgGs - (3GdYQHj(B, (3HhMShfs ((3JdeSGf(B:s (3GdecJH GdLGeYj GdMOjK(B,s, 2017)
-(3JMdjd GdeaGgje GdGfKQHhdhLjI hGdGbJUGOjI (B-(3XQha fTCI GdGfKQHhdhLjI GdGbJUGOjI hJMOjO eaghegG (B-(3GdGJLGgGJ GdfXQjI aj GdCfKQHhdhLjG GdGbJUGOjI (B-(3GdJHGOd Hjf GdQeRj hGdGbJUGOj(B.s
(3HHdjhZQGajG(B:(3U(B.205s
Keywords: (3GdCfKQHhdhLjG GdGbJUGOjIs